Peran Bank Wakaf dalam Penguatan Ekonomi Islam: Sebuah Kerangka Konseptual - Afada, Abik; Budiyono (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
Abstract: This paper explores the concept and potential role of a Waqf Bank as a key institution in supporting the Islamic economy. By leveraging the traditional Islamic endowment system (waqf), a Waqf Bank could serve as a sustainable financial mechanism aimed at empowering Small and Medium Enterprises (SMEs), alleviating poverty, and promoting socio-economic development in Muslim-majority countries. This study employs a conceptual approach, drawing from both classical and contemporary literature on waqf and Islamic banking. It proposes a model where Waqf Bank operations align with Sharia principles while addressing modern economic challenges, such as financial inclusion and social welfare improvement. The findings suggest that a well-structured Waqf Bank has the potential to fill existing gaps in Islamic finance, providing a strategic means for wealth redistribution and long-term economic sustainability. The paper also highlights potential challenges in implementing such a bank, including legal, regulatory, and operational concerns, and offers recommendations for future research on optimizing waqf-based financial institutions.